MOBILE APP EDUCATION GANGGUAN PENCERNAAN MANUSIA BERBASIS MULTIMEDIA MENGGUNAKAN ADOBE ANIMATE CC - Samsudin Samsudin; Muhammad Dedi Irawan; Ahmad Hariandy Harahap (Universitas Asahan, 2019)
Abstract - Technological progress is changing very rapidly from year to year, mobile devices are one of the fastest growing technological products in its development, with the development of cellular technology at this time, which causes many changes, including in the world of education. Using mobile applications as learning tools can benefit from the availability of learning material that can be accessed at any time, and visualization of interesting material. the problem that arises is the lack of time for communication between teacher and students and learning that is still used by the media of books, which are mainly presented in the form of text, making students less attractive for further lessons. Therefore, researchers have developed educational applications to increase student motivation. Adobe Animate CC software is used to develop mobile multimedia applications to teach the human digestive system and multimedia disorders, this application is intended as an alternative source of student learning, so this application stimulates student motivation so students can play and learn on their own in their free time. Abstract - Kemajuan teknologi berubah sangat cepat dari tahun ke tahun, perangkat seluler adalah salah satu produk teknologi yang tumbuh paling cepat dalam perkembangannya, dengan perkembangan teknologi seluler saat ini, yang menyebabkan banyak perubahan, termasuk di dunia pendidikan. Menggunakan aplikasi seluler sebagai alat pembelajaran dapat mengambil manfaat dari ketersediaan materi pembelajaran yang dapat diakses kapan saja, dan visualisasi materi yang menarik. masalah yang muncul adalah kurangnya waktu untuk komunikasi antara guru dan siswa dan pembelajaran yang masih menggunakan oleh media buku, yang terutama disajikan dalam bentuk teks, membuat siswa kurang menarik untuk pelajaran selanjutnya. Oleh karena itu, peneliti telah mengembangkan aplikasi edukasi untuk meningkatkan motivasi siswa. Perangkat lunak Adobe Animate CC digunakan untuk mengembangkan aplikasi multimedia bergerak untuk mengajar sistem pencernaan manusia dan gangguan multimedia, aplikasi ini dimaksudkan sebagai alternatif sumber belajar siswa, sehingga aplikasi ini merangsang motivasi siswa agar siswa dapat bermain dan belajar sendiri pada waktu luang mereka.